KARAKTERISTIK PENGGERGAJIAN DAN PEMESINAN KAYU AREN (ARENGA PINNATA) - Osly Rachman; Dede Rohadi; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This paper discuses the results of study on the sawing and machining characteristics of aren wood (Arenga pinnata). The material used in this study consisted of 26 logs with diameter ranging from 23 cm to 42 cm. These logs were sawn using two cutting patterns, namely live sawing and round sawing. The parameters observed in the sawing procees comprised recovery, productivity and power consumption. .The result of statistical analysis reveals non significant differences of the effect of the two cutting patterns on sawing recovery and sawing productivity. On the other hand, the location of bolt within the stem does not seem to have significant effect on power consumption. The average values of recovery, sawing productivity and power consumption of Aren stem are respectively 13,48%, 6,09 m3/hour and 64,92 watt sec./cm2.The machining characteristic of aren wood was tested in accordance with the modified ASTM D- 1666 (64).The material for the test consisted of 25 samples for each machining property tested (planing, shaping, turning, boring and sanding). The result shows that aren wood has good to very good machining characteristic especially in planing, shaping, boring and sanding.